Effect of implantation Ti-6Al-4V ELI in femoral bone defect regeneration of Sprague Dawley rat - I Nyoman Jujur; Damisih; Kartika Devy; Shovy Suha; Boy Muchlis Bachtiar; Endang Winiati Bachtiar (Wolters Kluwer Medknow Publications, 2020)
Ti-6Al-4V ELI is one of the most commonly used dental implant restore function. The solution treatment temperature variation can significantly increase the strength, but it is not yet known the effect of these temperature variations on the alloy's biocompatibility properties. Twelve female Sprague Dawley rats were divided into six groups as follows: the treated group, the control group, and the defect group without implant material. In the treated group, the femur bone defect was implanted with as-cast Ti-6Al-4V ELI, 850°C, 950°C, and 1050°C heat-treated Ti-6Al-4V ELI implant material. The rats were euthanized after 30 days postimplantation and evaluated histologically. The results show that the histological scoring of the specimen for femur defect without implant material is 2 (fibrous union and fibrocartilaginous), score with implant as-cast is 2.5, the sample with 850°C heat treatment material is 2.5, 950°C is 2.5, and the temperature at 1050°C is 2.5. The score of 2.5 is between score 2 and score 3: hemorrhage, fibrous union, fibrocartilaginous microhemorrhage, and mineralized cartilage union. In conclusion, there is no effect of different heat treatment temperatures for Ti-6Al-4V ELI implant material in rat bone regeneration's maturation level.